The Implementation of Different Types of Rubrics in a Hong Kong Secondary School - Chu, Ho Shing (Universitas Negeri Malang, 2022)
Rubrics were traditionally a perfect choice for assessing performance. Yet, most rubrics and previous research only focused on its traditional summative aspect, limiting its functions, or even leading to some inappropriate usage or misconception of using rubrics. As formative assessment was found to favor low-achieving students, it has become increasingly popular that rubrics can also be used for formative use and help reduce learning diversity. In this study, different types of rubrics in a Hong Kong Secondary School were investigated, which has been a popular tool that has been widely used among various subjects as an assessment tool. The classification of the rubrics based on different learning areas unveiled that distinct learning areas tended to use heterogeneous rubrics, so the implementation and learning outcomes were then reviewed. It was also noted that a rubric was used for formative assessment in a newly developed STEM curriculum, hence the effectiveness was examined.